2016
DOI: 10.1155/2016/6430156
|View full text |Cite
|
Sign up to set email alerts
|

A Case of New-Onset Dermatomyositis in the Second Trimester of Pregnancy: A Case Report and Review of the Literature

Abstract: Dermatomyositis (DM), a subtype of idiopathic inflammatory myopathies (IIMs), is characterized by skin rash, proximal muscle weakness, and inflammatory infiltrates in the muscle tissue. The peak incidence of the disease is at the age of 50–60 years, and only 14% of the patients with IIMs are estimated to present during reproductive years. Because of the limited pregnancy experience in patients with IIMs, little is known regarding the effects of DM on pregnancy or vice versa. We herein report a 40-year-old woma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Treatment regimen should consider the safety of both the mother and the fetus, which requires individualized therapy. Glucocorticoids are the first line treatment in pregnant patients with DM (24). In certain rare cases, the use of glucocorticoids has been demonstrated to lead to a good outcome (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment regimen should consider the safety of both the mother and the fetus, which requires individualized therapy. Glucocorticoids are the first line treatment in pregnant patients with DM (24). In certain rare cases, the use of glucocorticoids has been demonstrated to lead to a good outcome (6).…”
Section: Discussionmentioning
confidence: 99%
“…In certain rare cases, the use of glucocorticoids has been demonstrated to lead to a good outcome (6). However, certain patients have been shown to be non-responsive or intolerant to glucocorticoids (24). A previous study illustrated that gestational exposure to glucocorticoids led to a slight increase in the risk of premature birth and fetal oral cleft (25).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the risks might be overestimated as the study required hospitalization for IIM, which might lead to selection of women with high disease activity/severity in that study. In several small scale clinic-based studies and in a review, higher risk of preterm birth was associated with active disease status [ 2 , 4 , 5 , 27 ]. We identified women with IIM from both inpatient and outpatient clinics, and therefore disease activity may have varied from mild to severe, which might explain the difference between our findings and the Australian study although our study did not find any different risk estimates among births to women with IIM identified from the inpatient vs the outpatient register.…”
Section: Discussionmentioning
confidence: 99%
“…Katz [ 2 ] and Morihara et al [ 3 ] have described a relationship between autoimmune myositis (myopathy) and pregnancy as attributable to changes in the mother's hormones or the fetus being recognized as a foreign body. Missumi et al [ 4 ] reported in their case series covering 15 cases that the disease activity of myositis does not increase because of pregnancy; however, several other reports have associated the disease activity of myositis with fetal prognosis, and it has, moreover, been associated with higher rates of preeclampsia, preterm birth, or fetal death [ 5 7 ]. According to these reports, favorable control of disease activity before or during pregnancy would likely improve the prognosis of both the mother and child in pregnancies complicated with autoimmune myositis (myopathy).…”
Section: Discussionmentioning
confidence: 99%